Qiita Teams that are logged in
You are not logged in to any team

Community
Service
Qiita JobsQiita ZineQiita Blog
0
Help us understand the problem. What is going on with this article?
@campbel2525

# ベクトル解析公式集

More than 1 year has passed since last update.

## 概要

ベクトル公式です。ベクトルの演習は公式を覚えれば簡単ですよ。

## 基本的な公式

    \boldsymbol{ a } \times (\boldsymbol{ b } \times \boldsymbol{ c }) = (\boldsymbol{ a } \cdot \boldsymbol{ c })\boldsymbol{ b } - (\boldsymbol{ a } \cdot \boldsymbol{ b })\boldsymbol{ c }

    (\boldsymbol{ a } \times \boldsymbol{ b }) \times \boldsymbol{ c } = (\boldsymbol{ a } \cdot \boldsymbol{ c })\boldsymbol{ b } - (\boldsymbol{ b } \cdot \boldsymbol{ c })\boldsymbol{ a }

    (\boldsymbol{ a },\boldsymbol{ b },\boldsymbol{ c }) = \boldsymbol{  } \cdot (\boldsymbol{ b } \times \boldsymbol{ c }) = \begin{vmatrix} a_1 & a_2 & a_3 \\ b_1 & b_2 &b_3 \\ c_1 & c_2 &c_3 \end{vmatrix}

    \nabla (fg) = (\nabla f)g + f(\nabla g)

    \nabla (\frac{ f }{ g }) = \frac{ f (\nabla f)g - f(\nabla g)}{ g^2 }

    \nabla (\varphi (f)) = \varphi '(f) \nabla \varphi (f)

    \nabla (f \boldsymbol{ F }) = (\nabla f) \cdot \boldsymbol{ F } + f(\nabla f \cdot \boldsymbol{ F })

    \nabla \times (f \boldsymbol{ F }) = (\nabla f) \times \boldsymbol{ F } + f(\nabla f \times \boldsymbol{ F })

    \nabla ^2 f = f''(r) + \frac{ 2 }{ r } f'(r)

    \nabla (\boldsymbol{ F } \cdot \boldsymbol{ G }) = (\boldsymbol{ G } \cdot \nabla) \boldsymbol{ F } + (\boldsymbol{ F } \cdot \nabla) \boldsymbol{ G } + \boldsymbol{ F } \times (\nabla \times \boldsymbol{ G }) + \boldsymbol{ G } \times (\nabla \times \boldsymbol{ F })

    \nabla \cdot (\boldsymbol{ F } \times \boldsymbol{ G }) = (\nabla \times \boldsymbol{ F }) - \boldsymbol{ F } \cdot (\nabla \times \boldsymbol{ G })

    \nabla \times (\boldsymbol{ F } \times \boldsymbol{ G }) = (\nabla \cdot \boldsymbol{ G }) \boldsymbol{ F } - (\nabla \cdot \boldsymbol{ F }) \boldsymbol{ G } + (\boldsymbol{ G } \cdot \nabla) \boldsymbol( F ) - (\boldsymbol{ F } \cdot \nabla) \boldsymbol( G )

    \nabla r^α = αr^{α-2} \boldsymbol{ r }

    \Delta r^α = α(α + 1)r^{α - 2}

    \nabla \cdot (r^α \boldsymbol{ r }) = (α + 3)r^α

    \nabla \log r = \frac{ \boldsymbol{ r } }{ r^2 }

    \nabla (\frac{ \boldsymbol{ r } }{ r }) = \frac{ 2 }{ r }

    \Delta (\frac{ 1 }{ r^2 }) = \frac{ 4 }{ r^4 }

    \nabla \times \boldsymbol{ r } = C

    \nabla \cdot (\nabla \times \boldsymbol{ F }) = 0

    \nabla \times (\nabla f) = \boldsymbol{ 0 }

    df = (\nabla f) \cdot d\boldsymbol{ r } = (d\boldsymbol{ r } \cdot \nabla)f

        \nabla \times (\nabla \times \boldsymbol{ F }) = \nabla (\nabla \cdot \boldsymbol{ F }) - \triangle \boldsymbol{ F }


    \Delta \boldsymbol{ F } = \Delta F_x \boldsymbol{ i } + \Delta F_y \boldsymbol{ j } + \Delta F_y \boldsymbol{ k }

    \begin{eqnarray}\Delta f = \nabla^2 f = \frac{ \partial^2 f }{ \partial x^2 }   + \frac{ \partial^2 f }{ \partial y^2 }   + \frac{ \partial^2 f }{ \partial z^2 }\end{eqnarray}


## 円柱座標

    u = (r, \theta, z)

    \nabla = ( \frac{ \partial }{ \partial r },  \frac{ 1 }{ r } \frac{ \partial }{ \partial \theta }, \frac{ \partial }{ \partial z })

    \nabla \cdot \boldsymbol{ A } = \frac{ 1 }{ r }\frac{ \partial }{ \partial r }(rA_r) + \frac{ 1 }{ r }\frac{ \partial }{ \partial \theta }(A_\theta) + \frac{ \partial }{ \partial z }(A_z)

    \nabla \times \boldsymbol{ A } =
{ \frac{ 1 }{ r } \frac{ \partial }{ \partial \theta }( A_z ) - \frac{ \partial }{ \partial \theta }(A_\theta)} \boldsymbol{ r }
+ { \frac{ \partial }{ \partial z }( A_r ) - \frac{ \partial }{ \partial r }(A_z)} \boldsymbol{ \theta }
+  \frac{ 1 }{ r } { \frac{ \partial }{ \partial z }( rA_r ) - \frac{ \partial }{ \partial \theta }(A_r)} \boldsymbol{ z }

    \Delta u = u_rr + \frac{ 1 }{ r } u_r + \frac{ 1 }{ r^2 }u_\theta\theta + u_zz

     \boldsymbol{ v } = \dot{ r }\boldsymbol{ r } + r\dot{ \theta }\boldsymbol{ \theta } + \dot{ z }\boldsymbol{ z }

     \boldsymbol{ a } = (\ddot{ r } - r\ddot{ \theta })\boldsymbol{ r } + \frac{ 1 }{ r }\frac{ d }{ dt }(r^2 \dot{ \theta })\boldsymbol{ \theta } + \ddot{ z }\boldsymbol{ z }


## 球座標

    u = (r, \theta, \phi)

    \Delta = (\frac{ \partial }{ \partial r}, \frac{ 1 }{ r }\frac{ \partial }{ \partial \theta}, \frac{ 1 }{ r\sin \theta })

    \nabla \cdot \boldsymbol{ A } = \frac{ 1 }{ r^2 } \frac{ \partial }{ \partial r }(r^2A_r) + \frac{ 1 }{ r\sin \theta }\frac{ \partial }{ \partial \theta }(A_\theta \sin \theta) + \frac{ 1 }{ r\sin \theta }\frac{ \partial }{ \partial \phi }(A_\phi)

    \nabla \times \boldsymbol{ A } = \frac{ 1 }{ r\sin \theta } { \frac{ \partial }{ \partial \theta}(A_\phi \sin \theta)- \frac{ \partial }{ \partial \theta}}\boldsymbol{ r }
\frac{ 1 }{ r } {\frac{ 1 }{ \sin \theta }\frac{ \partial }{ \partial \phi }(A_r)- \frac{ \partial }{ \partial r }(rA_\phi)}\boldsymbol{ \theta }
\frac{ 1 }{ r }{\frac{ \partial }{ \partial r}(rA_\theta)- \frac{ \partial }{ \partial \theta}(A_r)}\boldsymbol{ \theta }

    \boldsymbol{ v } = \dot{ r }\boldsymbol{ r }+ r\dot{ \theta }\boldsymbol{ \theta }+ r\sin \theta \dot{ \phi }\boldsymbol{ \phi }

    \boldsymbol{ a } = {\ddot{ r }- r\dot{\theta}^2- r\sin^2 \theta \dot{\phi}^2}\boldsymbol{ r }
+{\frac{ 1 }{ r }\frac{ d }{ dt }(r^2 \theta )- r\sin \theta \cos \theta \dot{\phi}^2}\boldsymbol{ \theta }
+{\frac{ 1 }{ r\sin \theta }\frac{ d }{ dt }(r^2 \sin^2\theta \dot{\phi})}\boldsymbol{ \phi }

0
Help us understand the problem. What is going on with this article?
Why not register and get more from Qiita?
1. We will deliver articles that match you
By following users and tags, you can catch up information on technical fields that you are interested in as a whole
2. you can read useful information later efficiently
By "stocking" the articles you like, you can search right away